Integrating Care for Mother?Infant Dyads After Preterm Birth: A Qualitative Study of Clinician Perspectives on Feasibility - Emily F. Gregory; Peter F. Cronholm; Lisa D. Levine; Rinad S. Beidas; Mario P. DeMarco; Ann L. O'Sullivan; Scott A. Lorch; Adya I. Maddox; Katherine Wu; Alexander G. Fiks (Mary Ann Liebert, 2023)
Objective: There are gaps in receipt of maternal preventive services in the interconception period. Yet mother?infant dyads have frequent health care visits. Health systems have opportunities to better capitalize on existing visits to address dyad needs, but this possibility has not been fully explored. Methods: In this qualitative study we conducted semistructured interviews with clinical team members involved with birthing parents or infants after preterm birth. We conducted snowball sampling from teams in pediatrics, obstetrics, and family medicine at two geographically adjacent health systems. Interviews explored perspectives on existing barriers and facilitators to integrating dyad care across adult and infant teams. Interviews were audio-recorded, professionally transcribed, and coded using an integrated approach. Results: We interviewed 24 physicians, nurses, midwives, and social workers (March?November 2021). Participants identified barriers to integrated care including infrequent communication between clinical teams, which was generalizable to care of the birthing parent or infant as individuals, and additional barriers related to privacy, credentialing, and visit design that were specific to dyad care. To improve integration of dyad care, clinicians proposed adapting a variety tools and procedures currently used in their practices, including electronic health record tools for communication, dedicated roles to support communication or navigation, centralized information on resources for dyad care, referral protocols, identifying dyads for proactive outreach, and opportunities for clinicians to connect face-to-face about shared patients or families. Conclusions: Clinicians believe existing health care structures and processes can be adapted to address current substantial barriers to integrated dyad care.